From technical to academic central banking: The scientization of the Banque de France - Maxence Dutilleul (Finance and Society)
This article documents the historical evolution of economic expertise at the Banque de France (BdF), from the late-nineteenth to early-twenty-first centuries. Criticizing presentism and conceptual reductionism in the notion of scientization, I characterize the evolution of economic expertise at the BdF as being a result of ‘field effects’ emerging from the BdF’s attempts to build state capacity. The BdF’s development of economics expertise should be interpreted as a way of negotiating the boundaries between various fields (private banking, technocracy, academia, and international central banking). In particular, I highlight two distinct boundary arrangements: technicalization and academization. From the late-nineteenth century to the 1960s, the rise of technical functions results from a dual positioning at the boundary between, respectively, the state and the market, and national and international institutions. The BdF’s nationalization, in the mid-twentieth century, fostered its integration into the administrative and technocratic field, putting it in competition with other ‘technicalized’ institutions. From the 1970s to the 1990s, the BdF negotiated new arrangements with the academic field. Finally, as a member of the European System of Central Banks since 1999, the BdF has sought scientific legitimacy to have a say in European monetary policymaking.